Exchange Rates, Nominal Inertia and Inflation. - Ireland, J; Wren-Lewis, S (1998)
This paper examines the use of the nominal exchange rate in achieving disinflation under managed exchange rate regimes. Most previous empirical studies have not explicitly identified expectations in the wage and price setting behavior of their econometric models, despite the importance of expectations both during a disinflation and in correcting misalignments. This has meant that costs due to nominal inertia and nonneutralities have not been addressed separately from questions of credibility. The authors present results for the U.K. economy using both a theoretical and empirical model in which firms and workers form rational expectations, but where there is also nominal inertia. They identify costs in using the exchange rate to change the inflation rate, and also the costs involved in correcting any disequilibria in the real exchange rate.